The Outcomes and Success Rates of Kasai Operation for Biliary Atresia Cases Using Presurgical Hepatobiliary Scan: Observations at NINMAS (Bangladesh Journal of Nuclear Medicine, 2024)
Abstract not avaiableBangladesh J. Nuclear Med. 27(1): 44-48, 2024